Women as Sex Objects in Azizi Haji Abdullahâ€™s Novel Bila Hujan Malam: A Critical Appraisal - Tahir, National University of Malaysia (UKM), Ungku Maimunah Mohd. (Asiatic: IIUM Journal of English Language and Literature, 2011)
This article analyses Azizi Haji Abdullah's novel Bila Hujan Malam to determine critical claims of its literary merit. Using the analytical framework Persuratan Baru advanced by the local writer and critic, Mohd Affandi Hassan, that distinguishes between story and knowledge, the article unpacks â€œwomen as sex objectsâ€ as the novel's main perception, which Azizi structures into the story by means of four narrative strategies. The strategies centre round firstly, using selected aspects of the â€œunexplained antecedentâ€ technique, secondly, making molestation that strips women of control and agency as the only form of sexual union available, thirdly, providing a context conducive to sexual exploitation, and fourthly, denying a role for women other than that of a sex object. The article argues that, contrary to claims of its literary merit, the novel prioritises iniquity as a valid aesthetic and literary expression, at the same time as it makes discourse/knowledge irrelevant to its structuring. In so doing, it operates as a novel only on the level of story and story making. This article thus concludes that Bila Hujan Malam is no more than an erotic novel. It also calls into question several literary conventions regarded as mainstream in Malay literature.